THE METHODOLOGY OF TEACHING INTERESTING MATHEMATICAL PROBLEMS IN GENERAL EDUCATION SCHOOLS - Mamatova Zilolakhon Khabibullohonovna; Abdumajidova Mukarramkhon Iqboljon qizi (TADQIQOTLAR, 2025)
Annotation This article examines the methodology of using interesting problems in teaching mathematics in general education schools and analyzes their role in enhancing students’ mathematical thinking, logical reasoning, creativity, and motivation. The paper discusses various types of engaging problems, the criteria for selecting them, and the ways to integrate them into the teaching process. In addition, interactive methods, effective strategies, and practical recommendations for working with such problems are presented.